Influence of a perpendicular magnetic field on biological effectiveness of carbon-ion beams. (2nd September 2019) - Inaniwa, Taku; Suzuki, Masao; Sato, Shinji; Noda, Akira; Muramatsu, Masayuki; Iwata, Yoshiyuki; Kanematsu, Nobuyuki; Shirai, Toshiyuki; Noda, Koji
Abstract: Purpose: Our previous study revealed that the application of a magnetic field longitudinal to a carbon-ion beam of 0.1 ≤ B // ≤ 0.6 T enhances the biological effectiveness of the radiation. The purpose of this study is to experimentally verify whether the application of a magnetic field perpendicular to the beam also alters the biological effectiveness. Methods and materials: Most experimental conditions other than the magnetic field direction were the same as those used in the previous study to allow comparison of their results. Human cancer and normal cells were exposed to low (12 keV/μm) and high (50 keV/μm) linear energy transfer (LET) carbon-ion beams under the perpendicular magnetic fields of B ⊥ = 0, 0.15, 0.3, or 0.6 T generated by a dipole magnet. The effects of the magnetic fields on the biological effectiveness were evaluated by clonogenic cell survival. Doses that would result in the survival of 10%, D 10 s, were determined for the exposures and analyzed using Student's t -tests. Results: For both cancer and normal cells treated by low- and high-LET carbon-ion beams, the D 10 s measured in the presence of the perpendicular magnetic fields of B ⊥ ≥ 0.15 T were not statistically different ( p ≫ .05) from the D 10 s measured in the absence of the magnetic fields, B ⊥ = 0 T. Conclusions: Exposure of human cancer and normal cells to the perpendicular magnetic fields of B ⊥ ≤ 0.6 T did not alter significantly the biological effectiveness of the carbon-ion beams, unlike the exposure to longitudinal magnetic fields of the same strength. Although the mechanisms underlying the observed results still require further exploration, these findings indicate that the influence of the magnetic field on biological effectiveness of the carbon-ion beam depends on the applied field direction with respect to the beam.